CRISPR-Cas9–based gene editing as a proof-of-concept approach in an inborn error of immunity caused by a DCLRE1C variant - Tugce Duran; Mehmet Ali Karaselek; Burak Dagdelen; Serkan Kuccukturk; Sükrü Nail Guner; Sevgi Keles; Ismail Reisli (Immunologic Research, 2026)
Hypomorphic DCLRE1C variants impair T and B cell development, leading to combined immunodeficiency (CID) or leaky severe combined immunodeficiency (SCID). Current treatment options, such as allogeneic hematopoietic stem cell transplantation (aHSCT), are associated with significant risks, highlighting the need for alternative therapeutic strategies. In this study, we report the first a proof-of-concept CRISPR-Cas9–mediated correction of a hypomorphic DCLRE1C variant (c.194 C > T; p.T65I) in CD4 + helper T (Th) cells using CRISPR-Cas9 gene-editing technology. CD4 + Th cells were isolated, and the variant region was edited with sgRNA and donor DNA. Gene editing efficiency was confirmed by Sanger sequencing, revealing successful restoration of the target region to its wild-type sequence. Functional analyses showed a significant increase in CD25 activation and Artemis protein expression post-editing, although DCLRE1C mRNA levels remained unchanged. The approximately 6–8% increase in CD25 expression was statistically significant but did not reach healthy control levels. These findings suggest that CRISPR-Cas9 –mediated gene editing may enable precise correction and induce measurable cellular-level functional changes, supporting biological feasibility rather than therapeutic efficacy. This study provides a foundation for future research on HSCs and underscores the potential role of CRISPR-Cas9–based approaches in the treatment of inborn errors of immunity (IEIs) associated with DCLRE1C variants.

Pediatric selective IgM deficiency: clinical features and a preliminary risk index for immunoglobulin replacement therapy - Emine Ozdemir; Mehmet Ali Karaselek; Sukru Nail Guner; Sevgi Keles; Ismail Reisli (Immunologic Research, 2025)

Monocyte plasticity and HLA-DR expression in patients with X-linked agammaglobulinemia - Hasibe Artac; Ayca Ceylan; Ilknur Kulhas Celik; Figen Celebi Celik; Yasin Karali; Zeynep Meric; Demet Tekcan; Mehmet Geyik; Selcen Bozkurt; Saliha Esenboga; Zehra Şule Haskoloğlu; Esra Ozek Yucel; et al. (Immunologic Research, 2025)

Multi-class machine learning-based classification of SCID-related genetic variants - Ali Şahin; Gamze Sonmez; Mehmet Karaselek; İsmail Reisli (Immunologic Research, 2025)

Correction to: Primary antibody deficiencies in Turkey: molecular and clinical aspects - Sinem Firtina; Yuk Yin Ng; Ozden H. Ng; Ayca Kiykim; Esra Yucel Ozek; Manolya Kara; Elif Aydiner; Serdar Nepesov; Yildiz Camcioglu; Esra H. Sayar; Ezgi Yalcin Gungoren; Ismail Reisli; et al. (Immunologic Research, 2022)

Primary antibody deficiencies in Turkey: molecular and clinical aspects - Sinem Firtina; Yuk Yin Ng; Ozden H. Ng; Ayca Kiykim; Esra Yucel Ozek; Manolya Kara; Elif Aydiner; Serdar Nepesov; Yildiz Camcioglu; Esra H. Sayar; Ezgi Yalcin Gungoren; Ismail Reisli; et al. (Immunologic Research, 2022)